ANALISA TINGKAT KERUSAKAN PRODUKSI KEMASAN KARTON MENGGUNAKAN METODE SIX SIGMA DI PT XYZ - Goklas, Bonifasius Justin Abel; Adianto; Saryatmo, Mohammad Agung (Universitas Tarumanagara, 2025)
PT XYZ is a manufacturer engaged in the field of cardboard packaging producers. Cardboard products are needed by traders to wrap their products safely until they reach consumers. Cardboard packaging is often found in various forms of defects in its production. The increase in defect production is a concern because it is detrimental to the company. The study was conducted to help the company identify production defects that occur in the cardboard packaging printing process. The analysis in this study used descriptive quantitative methods and Six Sigma DMAIC. This study uses a number of data from field observations and interviews with company employees, as well as data documentation owned by the company. So this study was conducted to improve product quality, find out the causes of defects in the production process, and provide suggestions for improvements and control of product quality. Based on the results of the study, the highest type of defect was found in uneven gluing and asymmetrical cardboard cutting. The cause of this was due to human factors that did not pay attention to the company's operational standards and suboptimal procedure forms.